Evaluación de un spray antiséptico a base de ozono (10,15,20 mg) en caninos con problemas de gingivitis tipo 1 en la ciudad de Quito - Oñate Pazmiño, Gabriela Alejandra (2021)
The present research report had the objective of developing an ozone-based antiseptic spray in which the mg of ozone was evaluated in each of the treatments for gingivitis in canines. Each one was an experimental unit and comprised an age between 3 - 4 years of age with a high percentage of mongrel canines of 35% followed by the French Poodle breed with 30%, Pekingese with 25% and the Schnauzer and German Shepherd breed. with 5% and in terms of sex, there was a higher incidence of females than males, in females with 60% and males with 40%. This project was carried out in a period of time of 30 days with daily application of the spray, the experimental group consisted of 20 canines with the division of 4 groups and 5 dogs in each one and the treatments were divided as follows: T0: Water Double distilled, T1: 10 mg of ozone concentration, T2: 15 mg of ozone concentration T3: 20 mg of ozone concentration, the preparation of these treatments was ozonating the water Double distilled with a duration of 10, 15 and 20 minutes respectively and that the machine gives one mg of ozone per minute. The research techniques used were direct observation, documentary, practical and experimental using programs such as infostat and Excel to reflect the results. The highest incidence of bacteria was determined to be gram positive and negative cocci. Finally, it was established that the spray against cocci is effective in its three treatments to be able to be used as a dental prophylactic.